An experimental study on CO2 laser beam welding of AISI 304SS and Cu dissimilar pipes. (2016) - Sahu, Sushanta Kumar; Moharana, Bikash Ranjan; Shaibu, V.B.; Sahoo, Susanta Kumar
Effect of process parameters such as laser power and welding speed on CO2 laser beam welding (LBW) of commercially pure copper (Cu) pipes with AISI 304 stainless steel (SS) pipes is investigated in the present study. Laser power is varied from 1.5 to 3.5 kW; heat source velocity/scan speed is varied from 0.72 to 4.5 m/min; and beam diameter is maintained at 0.18 mm operating in Gaussian mode. The microstructural developments and mechanical properties of the welded samples are investigated. It is observed that acceptable microhardness values, across the weld pool and along the depth direction have been obtained, and those are found to be related to the temporal continuation and quenching of plasma. The mechanical properties in terms of tensile stress realised values up to 286.232 MPa and the fracture was observed to be outside the weld zone. The growth of keyhole phenomena has been simulated and compared with experiment.